Роль фитохрома B в регуляции метаболических реакций фотосинтетического аппарата арабидопсиса дикого типа и мутанта hy2 - Кособрюхов, А.А.; Креславский, В.Д.; Ширшикова, Г.Н. (Фактори експериментальної еволюції організмів, 2014)
Aims. To improve understanding of the roles of phytochrom B in the regulation of metabolic reactions of photosynthetic apparatus of Arabidopsis thaliana wild type and mutant hy2 upon treatment of UV-B radiation. Methods. The activity of photosynthesis apparatus was measured by LCPro+ Portable Photosynthetic System. The rate of different stages carboxylation reaction were estimated according Farquhar model. Results. Arabidopsis thaliana wild type showed higher resistance to UV-A radiation compared with hy2 mutant. Conclusions. The formation of mechanisms of higher resistance to UV-A is due to active participation of PhyB form.

Key words: Arabidopsis taliana, UV-A tolerance, net photosynthetic rate, carboxylation rate, maximum electron transport rate, TPU utilization.